Sphaerae mundi : early globes at the Stewart Museum (Septentrion, 2000)
""Contents""; ""Foreword""; ""Preface""; ""Introduction""; ""An Art Historian's Approach to Globes""; ""CHAPTER 1 Globes from The Netherlands""; ""Introduction""; ""A Pair of Globes by the Blaeu Family: Terrestrial, Circa 1645-48, and Celestial, After 1630""; ""Globes by Gerard and Leonard Valk, Circa 1701-50""; ""Gerard Valk's 1701 Pair of Globes, Reissued Circa 1750""; ""A Valk Celestial Globe, Circa 1745, Set in an Early-Nineteenth-Century Planetarium by A. and J. van Laun""; ""An Anonymous Star Globe, Eighteenth Century""; ""CHAPTER 2 Globes from England""; ""Introduction""